The use of the concept of Bobath in improving patients of quantitative disorders of consciousness - K. Nicpoń-Nożewska; K. W. Nicpoń; A. Miler; M. Podhorecka; W. Zukow (Journal of Education, Health and Sport, 2017)
Patients reduced states of consciousness, because of excessive duration and severity of illness require particular care effects in all aspects of medical applications. The process of medical rehabilitation in these cases comes up against difficulties related to the lack or limitation of the interaction between the therapist and the patient. For these reasons, always seek individual respiratory effects on the brain of the patient in order to most effectively induce Neuroplastic processes. It appears that the concept of Bobath may be a method of realization of the therapeutic agents in patients who are limited consciousness. It is understood that the method in accordance with the concept of physiotherapy Bobath comes down more to learn the patient feel performed passively or actively moving, not only to indicate to him how this movement should look like. Patients remaining in the states of limited consciousness are a unique group in which the interpretation of receipt by them of external stimuli is problematic and often impossible to determine. Regardless of whether the consciousness of the patient is under the control of, or is disabled, body position and movement patterns performed in the framework of rehabilitation allow to receive mechanical stimuli, thus contributing to the implementation of the appropriate movement patterns or even - to eliminate abnormal patterns. Possibly the quick implementation of rehabilitation Bobath method seems to be particularly important in patients who have suffered injuries of the central nervous system were in a coma or minimal consciousness.